Socioeconomic Status of Women Entrepreneurs in Kerala and Tamil Nadu - S., Santha (Prabandhan: Indian Journal of Management, 2013)
For sustained economic development and social justice, socioeconomic status of women should be improved along with that of the men folk. Socioeconomic freedom gives women the right to determine the course of their lives. Entrepreneurship enhances the social standing of women. Entrepreneurial activity is dependent on several complex economic, social, and psychological factors. Thus, for any attempt made to understand the entrepreneurial activity among women, an analysis of their socioeconomic status is necessary. The present study had been undertaken to assess the socioeconomic status of women entrepreneurs in Kerala and Tamil Nadu. The respondents of the study consisted of registered women entrepreneurs of both Kerala and Tamil Nadu . The sample consisted of 327 women entrepreneurs from Kerala and 160 women entrepreneurs from Tamil Nadu. For the purpose of analysis, statistical tools like percentages, rank test, chi-square test, and z-test were used. The study revealed that the women entrepreneurs in Kerala and Tamil Nadu were similar in the following aspects viz. decision-making power, power exercised in the business, degree of involvement in social activities, and reason for involvement in social activities. With respect to the economic status of women entrepreneurs, significant differences were perceived in their annual sales, income, expenditure, annual savings, amount invested in total assets, fixed assets, amount of working capital at their disposal, and also in the percentage change in total assets, fixed assets, annual income, and in annual savings.